(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this study was to determine chronic liver disease and its association with hepatitis C virus in patients with type 2 diabetes mellitus in our setup at DHQTH Bannu. Study Design: Descriptive / case series study. Place and Duration of Study: This study was conducted at the Department of Medicine, DHQ Teaching Hospital (DHDTH) Bannu, Khyber Pakhtunkhwa from Sep 2015 to Sep 2016. Materials and Methods: Data were collected from 53 patients already diagnosed as Type 2 diabetes mellitus for more than 10 years presented with symptoms and signs of CLD, from Sep 2015 to Sep 2016, through laboratory test, to note their cause of CLD. Results: Out of 53 T2DM patients, 29 patients were males (54.7%) and 24 (45.3%) were females. All of these were having increase ALT >60 IU/L and increased echogenicity of liver parenchyma. Out of these, 30 patients (56.6%) (19males,11females) were having HCV +ve, 5 patients (9.4%) (3males,2 females) HbsAg +ve, and 3 patients (5.7%) (2males,1female) were B&C -ve. While in the remaining, 3 patients (5.7%) (2males,1female) were having NASH, 2 patients (3.8%)(both females) were AIH(ANA+ve) and 10 patients (18.9%) (3males,7females) were having simple Steotosis (with only increase ALT and increased echogenicity). So overall 30 patients(56.6%) with T2DM with CLD were HCV +ve. Conclusion: In our set up, the major cause of CLD in T2DM was chronic HCV infection. Most of these patients were cirrhotic, which is an alarming situation and need proper planing by health care providers.